PENERAPAN PEMBELAJARAN MODEL ELICITING ACTIVITIES (MEAS) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Hedi Budiman; Khairunnisa Noor Syayyidah (Delta: Jurnal Ilmiah Pendidikan Matematika, 2018)
The research aims to determine the enhancement of students' mathematical thinking skills using the Model Eliciting Activities (MEA) approach and how students' attitudes toward the Model Eliciting Activities (MEA) approach learning. The research method used quasi experiment with research design nonequivalent control group design. This research was conducted in SMP Negeri Cianjur with population in 7th grade. The sample used class VII-4 as control class and class VII-9 as experiment class. The instrument was essay question to measure mathematical creative thinking ability and a questionnaire of attitude scale as non-test instrument. The results showed that the enhancement of students' mathematical creative thinking ability using the Model Eliciting Activities (MEA) approach was better than students using a scientific approach and most students attitude was positive response toward the Model Eliciting Activities (MEA) approach.